Застосування метода навчання лінійного порогового елемента в задачах ідентифікації джерел радіосигналів - Колесніков, О. М.; Єлізаренко, І. О. (ХНУРЕ, 2023)
Ensuring the effective use of the radio frequency spectrum requires the availability of up-to-date information about the actual state of its use. Obtaining such information is achieved by building automated information systems for radio frequency spectrum management and a radio control system. The technical basis of the radio control system is an automated radio frequency monitoring system, which includes both stationary and mobile radio monitoring stations and automated radio monitoring control systems The application of pattern recognition technology for the task of identifying sources of radio radiation signals is shown on the example of the method of learning a linear threshold element. Based on this, one of the promising areas of work in this field is the use of artificial neural networks, which will allow the implementation of a parallel distributed processor and ensure reliable automatic identification of sources of radio radiation signals.
Keywords: ідентифікації джерел радіосигналів; радіосигнал